055 An unusual presentation of SOD1-ALS: a case report. (29th July 2019) - MacDonald, Allycia; Dyke, Jason; Khangure, Simon; Kelly, Andrew
Abstract : Introduction: Approximately 10% of amyotrophic lateral sclerosis (ALS) cases are inherited, of which 20% are due to mutations in the superoxide dismutase-1 gene (SOD1). MRI abnormalities are not uncommon in ALS, and there have been previous case reports of peripheral nerve enhancement in patients with SOD1 mutations, typically attributed to rapid neuronal degeneration. Case: A 31-year-old previously well Malaysian woman presented with a 3 month history of progressive lower limb weakness, initially involving the right lower limb but progressing to involve the left, requiring the use of a walking aid. Initial examination demonstrated asymmetric upper and lower motor neuron signs in bilateral upper and lower limbs. EMG findings were of a severe pure motor axonal process. CSF examination revealed elevated protein without significant elevation of white cells. MRI brain and spine demonstrated smooth cauda-equina ventral nerve root thickening and enhancement. Treatment with intravenous immunoglobulin and high dose corticosteroid was commenced for a presumed inflammatory process, with no clinical improvement. A cauda-equina nerve root biopsy was performed, demonstrating features consistent with an immune-mediated demyelinating neuropathy. The patient continued to deteriorate, developing flaccid upper limb weakness and facial involvement. Plasma exchange, azathioprine, cyclophosphamide, and rituximab were sequentially administered over the following two months without altering the rate of disease progression. Genetic testing returned a positive SOD1 heterozygous gene mutation, confirming the diagnosis of ALS. Conclusions: We present a case of SOD1-ALS with atypical features on imaging and histopathology suggesting an underlying demyelinating process, expanding the known clinical spectrum of this mutation.